A brief cognitive therapy intervention for internalised stigma in acute inpatients who experience psychosis: A feasibility randomised controlled trial. (April 2018) - Wood, Lisa; Byrne, Rory; Enache, Gabriela; Morrison, Anthony P.
Abstract: Internalised stigma is problematic for people who experience psychosis therefore psychological interventions are required. This study examine the feasibility and acceptability of a brief Cognitive Behavioural Therapy (CBT) intervention for internalised stigma with psychiatric inpatients experiencing psychosis. A feasibility randomised controlled trial was conducted, comparing CBT with a psychoeducational (PE) control arm. Thirty participants (aged 18–65, with psychosis, and currently admitted to a psychiatric hospital) were randomised to one of two conditions. Participants were assessed at baseline, post-intervention (two weeks) and at follow-up (one month). Both interventions incorporated two hours of sessions over a two week period. The outcomes examined were internalised stigma (primary outcome), stigma, attitudes toward mental health problems, personal recovery, depression and self-esteem. Recruitment was conducted over a seven month period from five psychiatric wards. Forty five potential participants were approached and 30 (66%) consented to take part. Fifteen participants were randomised to CBT and 15 to PE. Feasibility data demonstrated that both the research process and interventions were feasible and acceptable. Examination of outcomes demonstrated that there was no identified benefit of one intervention type over another. There were no adverse events related to study participation. A future definitive trial is required with improved methodological rigor. Highlights: Delivering a small scale randomised controlled trial (RCT) with acute psychiatric inpatients experiencing psychosis is feasible and acceptable. Both interventions were feasible and acceptable as indicated by participants' adherence to treatment, service user feedback, and examination of primary and secondary outcomes. The research procedure was feasible and acceptable as indicated by recruitment rates, consent rates and willingness of clinician's to refer participants.